Data-driven research on chemical features of Jingdezhen and Longquan celadon by energy dispersive X-ray fluorescence. Issue 4 (March 2016) - He, Ziyang; Zhang, Maolin; Zhang, Haozhe
Abstract: The energy dispersive X-ray fluorescence (EDXRF) is used to determine the chemical composition of celadon body and glaze in Longquan kiln (at Dayao County) and Jingdezhen kiln. Forty typical shards in four cultural eras were selected to investigate the raw materials and firing technology. Random forests, a relatively new statistical technique, has been adopted to identify chemical elements that are strongest explanatory variables to classify samples into different cultural eras and kilns. The results indicated that the contents of Na2 O, Fe2 O3, TiO2, SiO2 and CaO vary in celadon bodies from Longquan and Jingdezhen, which implies that local clay was used to manufacture celadon bodies in Jingdezhen kiln. By comparing the chemical composition in glaze, we find that the chemical elements and firing technology of Jingdezhen kiln are very similar to those in Longquan kiln, especially for Ming dynasty. This study reveals the inheritance between Jingdezhen kiln and Longquan kiln, and explains the differences between two kilns.